Short Communication: Efficacy of Two Commercial Disinfectants on Paenibacillus larvae Spores - Kiriamburi, Joseph; Muturi, Jamleck; Mugweru, Julius; Forsgren, Eva; Nilsson, Anna (Frontiers in Veterinary Science, 2022)
Paenibacillus larvae is a spore-forming bacterium causing American foulbrood (AFB) in honey bee larvae. The remains of a diseased larva contains billions of extremely resilient P. larvae spores viable for decades. Burning clinically symptomatic colonies is widely considered the only workable strategy to prevent further spread of the disease, and the management practices used for decontamination requires high concentrations of chemicals or special equipment. The aim of this study was to test and compare the biocidal effect of two commercially available disinfectants, “Disinfection for beekeeping” and Virkon S on P. larvae. The two products were applied to P. larvae spores in suspension as well as inoculated on two common beehive materials, wood and styrofoam. “Disinfection for beekeeping” had a 100 % biocidal effect on P. larvae spores in suspension compared to 87.0-88.6 % for Virkon S which, however, had a significantly better effect on P. larvae on styrofoam. The two disinfectants had similar effect on infected wood material.